Assessment of Financial Performance Using Financial Statement Analysis: Evidence from PT Astra Internasional Tbk - Anglina, Eva Rianty; Maduwu, Wilhelmus; Edward Alezandro Lbn. Raja (Universitas Pendidikan Ganesha, 2025)
This study addresses a critical gap in understanding the long-term impact of the COVID-19 pandemic on the financial strategies of large corporations in Indonesia. This research aims to analyze the financial performance of PT Astra Internasional Tbk during the period 2020–2024 through a financial statement analysis approach. The main focus of the research is directed at the use of financial ratios, such as liquidity, solvency, activity, and profitability ratios, to obtain a comprehensive picture of the company's financial condition. The research method used is a case study with a quantitative descriptive approach, which processes secondary data in the form of the company's annual financial statements. The results of the analysis show that there are dynamics of financial performance influenced by macroeconomic conditions, the COVID-19 pandemic, and the national economic recovery in the following period. The liquidity and solvency ratio shows the company's ability to maintain financial stability, while the profitability ratio emphasizes the efficiency of management in generating profits. On the other hand, fluctuations in activity ratios indicate challenges in optimizing asset utilization. Overall, PT Astra Internasional Tbk managed to maintain a relatively stable financial performance with a positive growth trend at the end of the analysis period. These findings confirm that the analysis of financial statements is an important instrument in assessing the financial health of the company, as well as providing strategic information for investors, creditors, and management in decision-making.